2004
DOI: 10.1002/cvde.200306310
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Neodymium Oxide This Films by Liquid Injection MOCVD Using a New Neodymium Alkoxide Precursor

Abstract: x , have been deposited by liquid injection MOCVD using the volatile gadolinium alkoxide precursor, [Gd(mmp) 3 ] (mmp = 1-methoxy-2-methyl-2-propanolate, OCMe 2 CH 2 OMe). Carbon-free GdO x films were grown over a wide range of substrate temperatures (300±600 C) on both Si(100) and GaAs(100) substrates. X-ray diffraction (XRD) data indicated that GdO x films grown on Si(100) were amorphous at low deposition temperatures, and crystalline with a C-type structure at growth temperatures of 450 C and above. GdO x f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…In the MOCVD data, the oxide growth rate from [Ce(mmp) 4 ] shows little sign of decrease above 600 8C. In contrast, complexes such as [La(mmp) 3 ] [16] and [Gd(mmp) 3 ] [17] show a rapid decrease in oxide growth rate above 500 8C, due to thermal depletion of the precursors on the reactor walls.…”
Section: )]mentioning
confidence: 71%
“…In the MOCVD data, the oxide growth rate from [Ce(mmp) 4 ] shows little sign of decrease above 600 8C. In contrast, complexes such as [La(mmp) 3 ] [16] and [Gd(mmp) 3 ] [17] show a rapid decrease in oxide growth rate above 500 8C, due to thermal depletion of the precursors on the reactor walls.…”
Section: )]mentioning
confidence: 71%
“…[77] Significantly, carbon was absent from all the films at the estimated AES detection limit of < 0.5 at.-%, even when the films were grown in the absence of O 2 . XRD data for Gd 2 O 3 films showed that at growth temperatures above 450°C, the GdO x films were crystalline Gd 2 O 3 with a C-type structure exhibiting a preferred (111) orientation.…”
Section: Mocvd Of Gadolinium Oxidementioning
confidence: 96%
“…The XRD data of a Gd 2 O 3 film deposited on GaAs(100) at 450°C was dominated by the (222) reflection, indicating a strong preferred orientation or even a heteroepitaxial relation with the underlying GaAs. [77] SEM images of fracture cross-sections from Gd oxide films deposited at 450/C on GaAs(001) and Si(001) substrates showed that, in both cases, the microstructure is featureless on the micrometer scale.…”
Section: Mocvd Of Gadolinium Oxidementioning
confidence: 97%
See 2 more Smart Citations